Impact of a Lifestyle Modification Program on Menstrual Irregularity among Overweight or Obese Women with Polycystic Ovarian Syndrome - Tyseer Marzouk; Hanan Nabil; Mohammed Senna (Korean Society of Women Health Nursing, 2015)
PURPOSE: This study aimed to evaluate the impact of a lifestyle modification program on menstrual irregularity among overweight and obese women with polycystic ovarian syndrome. METHODS: A quasi experimental research design was used to conduct this study on 82 women with polycystic ovarian syndrome at the Gynecology and Obesity clinics of Mansoura University Hospital, Egypt. Two groups were included; the study group received a lifestyle modification program for 48 weeks, while the control group was not subjected to this program. Data collection was done for the following variables, a structured interview questionnaire was used to assess the women's general characteristics, menstrual patterns, and 24-hour dietary recall and the researcher took anthropometric measurements and assessed hirsutism by the Ferriman-Gallwey scale. RESULTS: After one year of lifestyle modification, the number of menstrual cycles significantly increased from 2.7+/-1.6 to 6.9+/-1.5 (t=12.26, p<.001) in the study group compared to insignificant minor changes among the control group (t=0.69, p=.488). Additionally, 58.5% were menstruating regularly compared to none in the control group (chi2=33.93, p<.001). CONCLUSION: Participating in a lifestyle modification program was effective in reducing menstrual cycle's irregularity among overweight and obese women with PCOS. Thus, it is recommended to motivate the nurses in counseling the PCOS women on lifestyle modifications.